Morphological and molecular differentiation in the rhodymenia corallina complex (Rhodymeniaceae, rhodophyta) from Central Peru [Diferenciación morfológica y molecular en el complejo rhodymenia corallina (Rhodymeniaceae, rhodophyta) de Perú Central] - Perez-Alania M. (2019)
Seven species of Rhodymenia have been recorded for the coast of Peru, where six of them grow on the central coast: R. corallina, R. howeana, R. multidigitata, R. flabellifolia, R. skottsbergii and R. californica. The most controversial taxonomically is R. corallina, from which R. howeana and R. multidigitata have been separated, only on the basis of external morphological characters (stipe form and frond habit). Recent and intensive collections of this species complex in the central coast of Peru (9°S to 15°S) have allowed gathering several morphotypes, evidencing high morphological variability, which makes difficult to differentiate each of the taxa involved. The aim of this work was to clarify the taxonomy of this complex by combining morphological data, both vegetative and reproductive, and genetic sequences through the use of rbcL and COI-5P markers. Specimens from Callao, type locality of R. howeana and R. multidigitata, were molecularly analyzed together with material from the central (Casma to Marcona, 9-15°S) and northern coast of Peru (Piura, 6°S), as well as northern Chile (Coquimbo, 30°S), solving two Rhodymenia groups. A first phylogenetic group, associated to R. corallina from Chile (Coquimbo, 30°S), is distributed along the entire Peruvian central coast (Casma to Marcona, 9-15°S), and a second group is restricted to the northern coast of Peru (Piura to Casma, 6-9°S). These groups differ in characters of external and reproductive morphology. Based on features of the tetrasporangial sori, R. howeana is recognized for northern Peru. © 2019, University of Valparaiso. All rights reserved.